Діагностика результативності та ефективності господарювання підприємства сфери послуг - Васильченко, Олена Олегівна; Vasylchenko, Olena (Запоріжжя : 2024, 2024)
UA: Розглянуто механізм здійснення діагностики результатів діяльності підприємства, що функціонує в сфері послуг. Застосовано методику VRIO-аналізу для визначення стратегічного статусу ресурсів підприємства. Проаналізовано показники експрес-діагностики економіко-фінансової діяльності підприємства. Проведено факторний аналіз економічної та фінансової рентабельності за моделлю DU PONT. EN: Setting objectives. In the economically developed countries of the world, the development of enterprises in the service sector primarily depends on a timely, complete and maximally adequate diagnosis of the results of their activities, which will make it possible to identify bottlenecks, find errors and determine ways to correct the situation, as well as highlight strengths, opportunities and reserves that will contribute to the formation of strategic behavior aimed at the further successful development of both the enterprise and the industry as a whole. The object of economic diagnostics can be any sphere or direction of activity. Modern economic science has at its disposal a large arsenal of methods and techniques for enterprise diagnostics. However, it is extremely important to choose those of them that are most suitable for the enterprise of the relevant industry and take into account its specifics. Research results. During the VRIO analysis, it was determined that the most important role in the company’s activity is played by the personnel, as well as the organizational and technical resources of the company. Express diagnostics using the analysis of coefficients made it possible to reveal a several-fold increase in indicators of operational activity, asset management, solvency of the enterprise and profitability, which indicates the constant development of the enterprise. The indicators of absolute liquidity and the amount of net working capital, which is related to investment in fixed assets, are decreasing. Analysis using the DuPont method made it possible to identify those indicators that had the greatest impact on the profitability of the company’s capital. The ratio of current liquidity, profitability of sales, the ratio of autonomy and the share of receivables in current assets had a positive effect. Their counterbalance was the coefficients of the ratio of loan and equity capital and turnover of receivables. The combined effect of factors made it possible to raise the level of profitability of the enterprise. Conclusion. The results of the conducted research showed the possibility of practical use of the proposed diagnostic techniques in the production and economic activity of enterprises in the service sector.
Diagnostics of performance and efficiency of management of service sector enterprises
Keywords: діагностика; експрес-діагностика; VRIO-аналіз; стратегічний статус ресурсів; коефіцієнтний аналіз; модель DU PONT; diagnostics; express diagnostics; VRIO-analysis; strategic status of resources; ratio analysis; DU PONTLUG model